Realities of work life balance in Nigeria: perceptions of role conflict and coping beliefs - Akanji, Babatunde (Business, Management and Economics Engineering, 2012)
The purpose of this study is to explore the perceptions of Work-Life Balance (WLB) practices in a developing nation of Nigeria. Evidently, on the threshold of widened globalization propensities, work-life research is beginning to spread outside the western context. Thus, a qualitative approach was employed by conducting 61 in-depth interviews with Nigerian employees (41 women and 20 men) working in frontline employments in the banking, telecommunications and insurance sectors about their perceptions of WLB. The findings showed that though conflict situations existed more than work-family enrichment, but under different circumstances due to the long legacy of national challenges facing Nigeria. The apparent role conflicts have generated various coping strategies adapted by participants of study to moderate their perceived work-life conflict and this paper seeks to add to the compendium of WLB discourse on a global scale by examining key barriers detected to hinder its workable practices in Nigeria.